Diagnostic spectrum and time intervals in Sweden's first diagnostic center for patients with nonspecific symptoms of cancer. (4th March 2019) - Stenman, Emelie; Palmér, Karolina; Rydén, Stefan; Sävblom, Charlotta; Svensson, Inga; Rose, Carsten; Ji, Jianguang; Nilbert, Mef; Sundquist, Jan
Abstract: Background: Fast-track referral is an increasingly used method for diagnostic evaluation of patients suspected of having cancer. This approach is challenging and not used as often for patients with only nonspecific symptoms. In order to expedite the diagnostics for these patients, we established Sweden's first Diagnostic Center (DC) focusing on outcomes related to diagnoses and diagnostic time intervals. Material and Methods: The study was designed as a prospective cohort study. Patients aged ≥18 years who presented in primary care with nonspecific symptoms of a serious disease were eligible for referral to the DC after having completed an initial investigation. Acceptable diagnostic time intervals were defined to be a maximum of 15 days in primary care and 22 days at the DC. Diagnostic outcome, length of diagnostic time intervals and patient satisfaction were evaluated. Results: A total of 290 patients were included in the study. Cancer was diagnosed in 22.1%, other diseases in 64.1%, and no diagnosis was identified in 13.8% of these patients. Patients diagnosed with cancer were older, had shorter patient interval (time from first symptom to help-seeking), shorter DC-interval (time from referral decision in primary care to diagnosis) and showed a greater number of symptoms compared to patients with no diagnosis. The median primary care interval was 21 days and the median DC interval was 11 days. Few symptoms, no diagnosis, female sex, longer patient interval, and incomplete investigations were associated with prolonged diagnostic time intervals. Patient satisfaction was high; 86% of patients reported a positive degree of satisfaction with the diagnostic procedures. Conclusions: We demonstrated that the DC concept is feasible with a diagnosis reached in 86.2% of the patients in addition to favorable diagnostic time intervals at the DC and a high degree of patient satisfaction. Trial registration: ClinicalTrials.gov identifier: NCT01709539.